Electrolyte additive and application

By using compounds with specific structures as additives in the lithium-ion battery electrolyte and introducing silicon-oxygen bonds and trifluoromethanesulfonyl groups, the problem of poor cycle performance of existing electrolyte additives under high-pressure and high-temperature conditions has been solved and achieved Better cycle performance and high temperature resistance.

CN119361827AActive Publication Date: 2025-01-24LIONGO (CHANGZHOU) NEW ENERGY CO LTD

Patent Information

Application Number
CN202411471972.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The existing lithium-ion battery electrolyte additives have poor circulation performance under high pressure and high temperature conditions, which cannot meet the working needs of lithium-ion batteries under high pressure and high temperature cycles.

Method used

Compounds with specific structures are used as electrolyte additives. By introducing silicon-oxygen bonds and trifluoromethanesulfonyl groups, the hydrolysis problem of phenylboronic acid functional groups is improved, and an inorganic boron-containing low-resistance CEI layer is formed on the surface of the cathode.

Benefits of technology

It improves the cycle performance of lithium-ion batteries under high-pressure and high-temperature conditions, extends the service life of battery capacity, and enhances the high-pressure resistance, oxidation resistance, and high-temperature resistance of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005097038490000011
    Figure BDA0005097038490000011
  • Figure BDA0005097038490000021
    Figure BDA0005097038490000021
  • Figure BDA0005097038490000041
    Figure BDA0005097038490000041
Patent Text Reader

Abstract

The invention provides an electrolyte additive. According to the high-voltage electrolyte for the high-nickel lithium ion battery, the problem of electrolyte deterioration caused by easy hydrolysis of phenylboronic acid functional groups is improved by introducing silicon-oxygen bonds, the application of the high-voltage electrolyte in battery circulation is expanded, the reaction of water or hydrofluoric acid and boron in the electrolyte is isolated through the large steric-hindrance effect of the silicon-oxygen groups, boron-oxygen bonds are reserved, and the service life of the high-voltage electrolyte is prolonged. Forming a uniform and thin inorganic boron-containing low-impedance CEI layer on the surface of the positive electrode; meanwhile, the trifluoromethanesulfonyl group can improve the high-temperature storage performance of the battery, and the additive is added into the non-aqueous organic solvent as a functional additive, so that the electrolyte has relatively high high-pressure resistance, oxidation resistance and high-temperature resistance, and the lithium ion battery containing the electrolyte has relatively good cycle performance at high pressure and high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to an electrolyte additive and application thereof. Background Art

[0002] As an important component of the electrolyte, electrolyte additives mainly form films at the interface between the positive and negative electrodes, thereby protecting the positive and negative electrodes of the battery. Currently, commercial electrolyte additives are divided into film-forming additives, water and acid removal additives, overcharge additives, etc. Electrolyte additives play a vital role in the specific capacity, operating temperature range, cycle efficiency and safety performance of the battery.

[0003] Among high-voltage electrolyte additives, phenyl borate esters are rarely used. This is because the hydrolysis rate of phenyl borate esters is very fast, causing the electrolyte to turn yellow and deteriorate and become ineffective. In turn, phenyl borate ester additives cause rapid loss of battery capacity and poor cycle performance under high voltage and high temperature, which cannot meet the working requirements of lithium-ion battery electrolytes that are often in high-voltage and high-temperature cycles.

[0004] Therefore, providing an electrolyte additive for lithium ion batteries having good cycle performance under high pressure and high temperature has become a problem to be solved. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide an electrolyte additive and its application. The electrolyte additive provided by the present invention is used in lithium-ion batteries, which can enable lithium-ion batteries to have good cycle performance under high pressure and high temperature conditions.

[0006] The present invention provides an electrolyte additive, which is selected from one or more compounds having structures shown in Formula A-1, Formula A-2 and Formula A-3:

[0007]

[0008] In Formula A-1, Formula A-2 and Formula A-3, R1 and R2 are each independently selected from trifluoromethanesulfonyl imide and borosilane.

[0009] Preferably, the electrolyte additive is selected from one or more of compound (I), compound (II) and compound (III);

[0010]

[0011] The present invention also provides a lithium ion battery electrolyte, comprising a lithium salt, a non-aqueous organic solvent and an electrolyte additive, wherein the electrolyte additive is selected from the above electrolyte additives.

[0012] Preferably, the lithium salt is selected from any one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate or lithium difluorobis(oxalatophosphate).

[0013] Preferably, the non-aqueous organic solvent is any one or more of an organic ester solvent, an ether solvent, a sulfone solvent or a nitrile solvent.

[0014] Preferably, the electrolyte additive further comprises a second additive, and the second additive is selected from vinylene carbonate, ethylene carbonate, propylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 1,4-butane sultone, 2,4-butane sultone, N-phenylbis(trifluoromethanesulfonyl)imide, phenyl methanesulfonate, hydroquinone difluorosulfonate, methylene disulfonate, 1,3,5-triallyl isocyanurate, hexadecene Any one or more of methylene diisocyanate, p-phenylene diisocyanate, isocyanoethyl methacrylate, 2,4-toluene diisocyanate, vinyl sulfate, vinyl disulfate, propylene sulfite, triallyl phosphate, tripropargyl phosphate, tris(trimethylsilane)borate, tris(trimethylsilane)phosphate, tris(vinyldimethylsilane)phosphate, propyl diprop-2-ynyl phosphate, ethyl diprop-2-ynyl phosphate or tetramethylmethylene diphosphate.

[0015] Preferably, the lithium-ion battery electrolyte comprises:

[0016] 10 to 16 parts by weight of a lithium salt;

[0017] 80 to 90 parts by weight of a non-aqueous organic solvent;

[0018] 0.1 to 10 parts by weight of electrolyte additives.

[0019] The present invention also provides a lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte is selected from the above-mentioned lithium ion battery electrolyte.

[0020] Preferably, the active material of the positive electrode is selected from any one of lithium cobalt oxide, lithium manganese oxide, ultra-high nickel ternary nickel cobalt manganese lithium, lithium nickel manganese oxide, lithium iron phosphate or lithium manganese iron phosphate, preferably ultra-high nickel ternary nickel cobalt manganese lithium;

[0021] Preferably, the active material of the negative electrode is selected from any one of artificial graphite, natural graphite, lithium titanate, metallic lithium, silicon-carbon composite material or silicon oxide; preferably artificial graphite;

[0022] Preferably, the diaphragm is selected from a polypropylene diaphragm or a polyethylene diaphragm; preferably a polyethylene diaphragm;

[0023] Preferably, the charge and discharge voltage of the lithium-ion battery is 3.0-4.2V.

[0024] Compared with the prior art, the present invention provides an electrolyte additive, which is selected from one or more of the compounds having the structures shown in formula A-1, formula A-2 and formula A-3: In formula A-1, formula A-2 and formula A-3, R1 and R2 are independently selected from trifluoromethanesulfonyl imide and borosilane. The present invention is used for high-voltage electrolyte of high-nickel lithium-ion battery, and improves the problem of easy hydrolysis of phenylboronic acid functional group leading to electrolyte deterioration by introducing silicon oxygen bond, and expands its application in battery cycle. The large steric effect of silicon oxygen group isolates the reaction of water or hydrofluoric acid and boron element in the electrolyte, retains the boro oxygen bond, and forms a uniform and thin inorganic boron-containing low-impedance CEI layer on the positive electrode surface; at the same time, the trifluoromethanesulfonyl group can improve the high-temperature storage performance of the battery, and the additive is added to the non-aqueous organic solvent as a functional additive, so that the electrolyte has high resistance to high pressure, oxidation and high temperature, so that the lithium-ion battery containing it has good cycle performance under high pressure and high temperature. DETAILED DESCRIPTION

[0025] The present invention provides an electrolyte additive, which is selected from one or more compounds having structures shown in Formula A-1, Formula A-2 and Formula A-3:

[0026]

[0027] In Formula A-1, Formula A-2 and Formula A-3, R1 and R2 are each independently selected from trifluoromethanesulfonyl imide and borosilane.

[0028] In some preferred embodiments of the present invention, the electrolyte additive is selected from one or more of compound (I), compound (II) and compound (III);

[0029]

[0030] The present invention also provides a method for preparing an electrolyte additive having the structures of compound (I), compound (II) and compound (III), comprising the following steps:

[0031] A) mixing an aminophenylboronic acid compound with trifluoromethanesulfonyl chloride to react to obtain an intermediate product;

[0032] B) reacting the intermediate product with hexamethyldisilazide to obtain an electrolyte additive having the structures of compound (I), compound (II) and compound (III).

[0033] In step A), the aminophenylboronic acid compound is selected from (4-aminophenyl)boric acid, (3-aminophenyl)boric acid, and (2-aminophenyl)boric acid.

[0034] In step A), the reaction medium is a mixed solution of NaH and THF, and the reaction process is carried out under nitrogen protection.

[0035] In step B), the catalyst of the reaction is selected from trimethylpentyl ammonium, the reaction temperature is 115° C., and the reaction time is 10 h.

[0036] The present invention also provides a lithium ion battery electrolyte, comprising a lithium salt, a non-aqueous organic solvent and an electrolyte additive, wherein the electrolyte additive is selected from the above electrolyte additives.

[0037] In the present invention, the lithium-ion battery electrolyte comprises:

[0038] 10 to 16 parts by weight of a lithium salt;

[0039] 80 to 90 parts by weight of a non-aqueous organic solvent;

[0040] 0.1 to 10 parts by weight of electrolyte additives.

[0041] Specifically, the lithium ion battery electrolyte includes 10 to 16 parts by weight of a lithium salt, which can be 10, 11, 12, 13, 14, 15, 16, or any value between 10 and 16 parts by weight. The lithium salt is selected from any one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bistrifluoromethylsulfonyl imide, lithium bisfluorosulfonyl imide, lithium bisoxalatoborate, lithium difluorooxalatoborate or lithium difluorobisoxalatephosphate, preferably lithium hexafluorophosphate.

[0042] The lithium-ion battery electrolyte further comprises 80 to 90 parts by weight of a non-aqueous organic solvent, which may be 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, or any value between 80 and 90 parts by weight. The non-aqueous organic solvent is any one or more of an organic ester solvent, an ether solvent, a sulfone solvent, or a nitrile solvent.

[0043] Wherein, the organic ester solvent is selected from one or more of ethylene carbonate, propylene carbonate, ethylene fluorocarbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, 1,4-butyrolactone, methyl formate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate or ethyl butyrate;

[0044] The ether solvent is selected from one or more of dimethyl ether, diethyl ether, methyl ethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether or 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether;

[0045] The sulfone solvent is selected from dimethyl sulfoxide and / or sulfolane;

[0046] The nitrile solvent is selected from any one or more of adiponitrile, succinonitrile or glutaronitrile.

[0047] The lithium-ion battery electrolyte also includes 0.1 to 10 parts by weight of an electrolyte additive, which can be 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or any value between 0.1 and 10 parts by weight, preferably any value between 0.1 and 5 parts by weight. The electrolyte additive is selected from the above-mentioned electrolyte additives. In some specific embodiments of the present invention, the electrolyte additive also includes a second additive, which is selected from vinylene carbonate, ethylene carbonate, propylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 1,4-butane sultone, 2,4-butane sultone, N-phenylbis(trifluoromethanesulfonyl)imide, phenyl methanesulfonate, hydroquinone difluorosulfonate, methanedisulfonic acid methylene ester, 1,3,5-triallyl isocyanurate, hexamethylene disulfonate Any one or more of isocyanate, p-phenylene diisocyanate, isocyanoethyl methacrylate, 2,4-toluene diisocyanate, vinyl sulfate, vinyl disulfate, propylene sulfite, triallyl phosphate, tripropargyl phosphate, tris(trimethylsilane)borate, tris(trimethylsilane)phosphate, tris(vinyldimethylsilane)phosphate, propyl diprop-2-ynyl phosphate, ethyl diprop-2-ynyl phosphate or tetramethylmethylene diphosphate, preferably 1,3-propane sultone (PS).

[0048] The present invention also provides a lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte is selected from the above-mentioned lithium ion battery electrolyte.

[0049] In the present invention, the active material of the positive electrode is selected from any one of lithium cobalt oxide, lithium manganese oxide, ultra-high nickel ternary nickel cobalt manganese lithium, lithium nickel manganese oxide, lithium iron phosphate or lithium iron manganese phosphate, preferably ultra-high nickel ternary nickel cobalt manganese lithium, and more preferably nickel cobalt manganese lithium NCM90.

[0050] The active material of the negative electrode is selected from any one of artificial graphite, natural graphite, lithium titanate, metallic lithium, silicon-carbon composite material or silicon oxide; preferably artificial graphite;

[0051] The diaphragm is selected from a polypropylene diaphragm or a polyethylene diaphragm, preferably a polyethylene diaphragm.

[0052] In the present invention, the lithium ion battery is preferably a high-nickel lithium ion battery.

[0053] In the present invention, the charging and discharging voltage of the lithium ion battery is 3.0-4.2V.

[0054] The invention is used for a high-voltage electrolyte of a high-nickel lithium-ion battery. The problem that the phenylboronic acid functional group is easily hydrolyzed and causes the electrolyte to deteriorate is improved by introducing a silicon-oxygen bond, and the application of the electrolyte in the battery cycle is expanded. The large steric hindrance effect of the silicon-oxygen group isolates the reaction between water or hydrofluoric acid in the electrolyte and the boron element, retains the boron-oxygen bond, and forms a uniform and thin inorganic boron-containing low-impedance CEI layer on the surface of the positive electrode. At the same time, the trifluoromethanesulfonyl group can improve the high-temperature storage performance of the battery. The additive is added to the non-aqueous organic solvent as a functional additive, so that the electrolyte has higher high-voltage resistance, oxidation resistance, and high-temperature resistance, so that the lithium-ion battery containing the trifluoromethanesulfonyl group has better cycle performance under high pressure and high temperature.

[0055] In order to further understand the present invention, the present invention is described below in conjunction with embodiments, and the protection scope of the present invention is not limited by the following embodiments.

[0056] Example 1

[0057] The specific steps for preparing compound (I) are as follows:

[0058]

[0059] First, NaH is added to THF and stirred for 10 minutes. Then, (4-aminophenyl)boric acid and trifluoromethanesulfonyl chloride are added dropwise at 0°C and added into a 250mL three-necked flask connected to nitrogen. After reacting for 1 hour, the mixture is cooled to room temperature and then allowed to stand for 12 hours to obtain product (I). After the product (I) is dried, hexamethyldisilazane is added to the product (I). The hexamethyldisilazane and the product (I) are reacted at 115°C for 10 hours under the catalysis of a small amount of trimethylpentylammonium. After cooling, the solid product is filtered to remove the solvent and impurities. The solid product is washed with ether to remove impurities and compound (I) is obtained after two distillations.

[0060] Prepare the electrolyte 1 sample, the specific steps are as follows:

[0061] In an argon glove box with a water and oxygen content of ≤0.1ppm, propylene carbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are uniformly mixed in a mass ratio of PC:DEC:EMC=10:25:50.5 to obtain an organic solvent, and then lithium hexafluorophosphate (LiPF6) is slowly added to the organic solvent. After complete dissolution, 1,3-propane sultone (PS) and compound (I) are added, and the electrolyte 1 is obtained after stirring. The amount of LiPF6, organic solvent, PS and compound (I) used is 13%, 85.5%, 1% and 0.5% of the total mass of the electrolyte, respectively.

[0062] Prepare the experimental battery 1 sample, the specific steps are as follows:

[0063] The positive electrode material nickel cobalt manganese lithium (NCM90), the conductive agent carbon black (SuperP), and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96.5:1.5:2, and N-methylpyrrolidone (NMP) is added after mixing to control the theoretical solid content to 55%. The positive electrode slurry is obtained by homogenization using a vacuum defoamer, and the positive electrode slurry is evenly coated on an aluminum foil with a thickness of 17 μm. After drying, rolling, and cutting, a 50 mm × 70 mm positive electrode sheet is obtained.

[0064] The negative electrode material artificial graphite, conductive agent SuperP, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) were mixed at a mass ratio of 95:1:1.5:2.5, and deionized water was added after mixing to control the theoretical solid content to 52%. The negative electrode slurry was homogenized using a vacuum defoamer, and the negative electrode slurry was evenly coated on a copper foil with a thickness of 17μm. After drying, rolling, and cutting, a 52mm×72mm negative electrode sheet was obtained. The N / P ratio of the positive and negative electrodes was 1.1.

[0065] The polyethylene diaphragm coated with nano-alumina was cut into a size of 55 mm × 75 mm and vacuum-baked at 70°C for 48 h to remove water.

[0066] A soft-pack laminated battery was made at an ambient dew point of ≤-45°C. The positive electrode sheet, separator, and negative electrode sheet were stacked in order, with the positive and negative electrode tabs on the same side, so that the separator was located between the positive and negative electrode sheets to play an isolating role, and a bare cell was obtained. The bare cell was placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, and then injected with the prepared electrolyte after cooling to below 40°C, followed by packaging, high-temperature infiltration, formation, aging, secondary vacuum packaging, and capacity division to obtain an experimental battery 1.

[0067] Example 2

[0068] The specific steps for preparing compound (II) are as follows:

[0069]

[0070] First, NaH was added to THF and stirred for 10 min. Then, (3-aminophenyl)boric acid and trifluoromethanesulfonyl chloride were added dropwise at 0°C and added to a 250 mL three-necked flask connected to nitrogen. After reacting for 1 h, the mixture was cooled to room temperature and then allowed to stand for 12 h to obtain product (II). After the product (II) was dried, hexamethyldisilazane was added to the product (II). The hexamethyldisilazane and the product (II) were reacted at 115°C for 10 h in the presence of a small amount of trimethylpentylammonium as a catalyst. After cooling, the solid product was filtered to remove the solvent and impurities. The solid product was washed with ether to remove impurities and compound (II) was obtained after two distillations.

[0071] Prepare the electrolyte 2 sample, the specific steps are as follows:

[0072] In an argon glove box with a water and oxygen content of ≤0.1ppm, propylene carbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are uniformly mixed in a mass ratio of PC:DEC:EMC=10:25:50.5 to obtain an organic solvent, and then lithium hexafluorophosphate (LiPF6) is slowly added to the organic solvent. After complete dissolution, 1,3-propane sultone (PS) and compound (II) are added, and the electrolyte 2 is obtained after stirring. The usage amounts of LiPF6, organic solvent, PS and compound (II) are 13%, 85.5%, 1% and 0.5% of the total mass of the electrolyte, respectively.

[0073] Prepare the experimental battery 2 sample, the specific steps are as follows:

[0074] The positive electrode material nickel cobalt manganese lithium (NCM90), the conductive agent carbon black (SuperP), and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96.5:1.5:2, and N-methylpyrrolidone (NMP) is added after mixing to control the theoretical solid content to 55%. The positive electrode slurry is obtained by homogenization using a vacuum defoamer, and the positive electrode slurry is evenly coated on an aluminum foil with a thickness of 17 μm. After drying, rolling, and cutting, a 50 mm × 70 mm positive electrode sheet is obtained.

[0075] The negative electrode material artificial graphite, conductive agent SuperP, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) were mixed at a mass ratio of 95:1:1.5:2.5, and deionized water was added after mixing to control the theoretical solid content to 52%. The negative electrode slurry was homogenized using a vacuum defoamer, and the negative electrode slurry was evenly coated on a copper foil with a thickness of 17μm. After drying, rolling, and cutting, a 52mm×72mm negative electrode sheet was obtained. The N / P ratio of the positive and negative electrodes was 1.1.

[0076] The polyethylene diaphragm coated with nano-alumina was cut into a size of 55 mm × 75 mm and vacuum-baked at 70°C for 48 h to remove water.

[0077] A soft-pack laminated battery was made at an ambient dew point of ≤-45°C. The positive electrode sheet, separator, and negative electrode sheet were stacked in order, with the positive and negative electrode tabs on the same side, so that the separator was located between the positive and negative electrode sheets to play an isolating role, and a bare cell was obtained. The bare cell was placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, and then injected with the prepared electrolyte after cooling to below 40°C, followed by packaging, high-temperature infiltration, formation, aging, secondary vacuum packaging, and capacity division to obtain experimental battery 2.

[0078] Example 3

[0079] The specific steps for preparing compound (III) are as follows:

[0080]

[0081] First, add NaH to THF and stir for 10 minutes. Then, add (2-aminophenyl)boric acid and trifluoromethanesulfonyl chloride dropwise at 0°C, add the mixture into a 250mL three-necked flask connected to nitrogen, react for 1 hour, cool to room temperature, and then let stand for 12 hours to obtain product (III). After the product (III) is dried, add hexamethyldisilazane to the product (III). The hexamethyldisilazane and the product (III) are reacted at 115°C for 10 hours under the catalysis of a small amount of trimethylpentylammonium. After cooling, filter the solid product to remove the solvent and impurities. Wash the solid product with ether to remove impurities, and obtain compound (III) after two distillations.

[0082] Prepare the electrolyte 3 sample, the specific steps are as follows:

[0083] In an argon glove box with a water and oxygen content of ≤0.1ppm, propylene carbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are uniformly mixed in a mass ratio of PC:DEC:EMC=10:25:50 to obtain an organic solvent, and then lithium hexafluorophosphate (LiPF6) is slowly added to the organic solvent. After complete dissolution, 1,3-propane sultone (PS) and compound (III) are added, and the electrolyte 3 is obtained after stirring. The usage amounts of LiPF6, organic solvent, PS and compound (III) are 13%, 85.5%, 1% and 0.5% of the total mass of the electrolyte, respectively.

[0084] Prepare the experimental battery 3 sample, the specific steps are as follows:

[0085] The positive electrode material nickel cobalt manganese lithium (NCM90), the conductive agent carbon black (SuperP), and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96.5:1.5:2, and N-methylpyrrolidone (NMP) is added after mixing to control the theoretical solid content to 55%. The positive electrode slurry is obtained by homogenization using a vacuum defoamer, and the positive electrode slurry is evenly coated on an aluminum foil with a thickness of 17 μm. After drying, rolling, and cutting, a 50 mm × 70 mm positive electrode sheet is obtained.

[0086] The negative electrode material artificial graphite, conductive agent SuperP, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) were mixed at a mass ratio of 95:1:1.5:2.5, and deionized water was added after mixing to control the theoretical solid content to 52%. The negative electrode slurry was homogenized using a vacuum defoamer, and the negative electrode slurry was evenly coated on a copper foil with a thickness of 17μm. After drying, rolling, and cutting, a 52mm×72mm negative electrode sheet was obtained. The N / P ratio of the positive and negative electrodes was 1.1.

[0087] The polyethylene diaphragm coated with nano-alumina was cut into a size of 55 mm × 75 mm and vacuum-baked at 70°C for 48 h to remove water.

[0088] A soft-pack laminated battery was made at an ambient dew point of ≤-45°C. The positive electrode sheet, separator, and negative electrode sheet were stacked in order, with the positive and negative electrode tabs on the same side, so that the separator was located between the positive and negative electrode sheets to play an isolating role, and a bare cell was obtained. The bare cell was placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, and then injected with the prepared electrolyte after cooling to below 40°C, followed by packaging, high-temperature infiltration, formation, aging, secondary vacuum packaging, and capacity division to obtain experimental battery 3.

[0089] Example 4

[0090] Compound (I), electrolyte 4 and experimental battery 4 were prepared according to the method of Example 1, except that the amount of additive compound (I) added to electrolyte 4 was 1%, wherein the amounts of LiPF6, organic solvent, PS and compound (I) used were 13%, 85%, 1% and 1% of the total mass of the electrolyte, respectively.

[0091] Example 5

[0092] Compound (II), electrolyte 5 and experimental battery 5 were prepared according to the method of Example 2, except that the amount of additive compound (II) added to electrolyte 5 was 1%, wherein the amounts of LiPF6, organic solvent, PS and compound (II) used were 13%, 85%, 1% and 1% of the total mass of the electrolyte, respectively.

[0093] Example 6

[0094] Compound (III), electrolyte 6 and experimental battery 6 were prepared according to the method of Example 3, except that the amount of additive compound (III) added to electrolyte 6 was 1%, wherein the amounts of LiPF6, organic solvent, PS and compound (III) used were 13%, 85%, 1% and 1% of the total mass of the electrolyte, respectively.

[0095] Comparative Example 1

[0096] Electrolyte 7 and experimental battery 7 were prepared according to the method of Example 1, except that trimethyl borate (TMB) was added as an additive to electrolyte 7, wherein the amounts of LiPF6, organic solvent, PS and trimethyl borate were 13%, 85%, 1% and 1% of the total mass of the electrolyte, respectively.

[0097] Comparative Example 2

[0098] Electrolyte 8 and experimental battery 8 were prepared according to the method of Example 1, except that the additive 3-cyano-5-fluorophenylboric acid (CFBA) was added to electrolyte 8, wherein the usage amounts of LiPF6, organic solvent, PS and trimethyl borate were 13%, 85%, 1% and 1% of the total mass of the electrolyte, respectively.

[0099] Comparative Example 3

[0100] Electrolyte 9 and experimental battery 9 were prepared according to the method of Example 1, except that the additive tri(2-cyanoethyl)borate (TB) was added to electrolyte 9, wherein the usage amounts of LiPF6, organic solvent, PS and trimethyl borate were 13%, 85%, 1% and 1% of the total mass of the electrolyte, respectively.

[0101] The soft-pack batteries prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to normal temperature and high temperature cycle performance tests and electrolyte acidity tests respectively:

[0102] Battery room temperature cycle test

[0103] The battery to be tested was placed in a constant temperature room at an ambient temperature of 25°C for 4 hours, then charged at a current of 1C and a voltage of 4.2V, with constant current and constant voltage until the cut-off current was 0.05C, and then discharged at a constant current of 1C to a voltage of 3V, and cycled for 500 cycles. The capacity retention rate was recorded, and the nth cycle capacity retention rate (%) = (nth cycle discharge specific capacity / first cycle discharge specific capacity) × 100%.

[0104] Battery high temperature cycle test:

[0105] In the test environment, the prepared soft-pack battery was placed in an explosion-proof test box at an ambient temperature of 45°C for 4 hours, and then charged at a constant current and constant voltage of 1C and 4.2V to a cut-off current of 0.05C, and then discharged at a constant current of 1C to a voltage of 3V. The cycle was repeated 500 times and the capacity retention rate was recorded. The capacity retention rate of the nth cycle (%) = (discharge specific capacity of the nth cycle / discharge specific capacity of the first cycle) × 100%.

[0106] Battery high temperature storage test

[0107] The battery to be tested is charged and discharged at room temperature for one week at a current of 1C, with a voltage range of 3 to 4.2V. The discharge capacity, internal resistance and volume of the first week are recorded. The internal resistance is tested using a battery internal resistance tester, and the volume is tested using the drainage method. Then charge to 4.2V at a constant current and constant voltage of 1C, with a cut-off current of 0.05C, and then the battery is placed in a constant temperature oven at 60°C for 7 days. After the time is up, take out the battery and cycle it at room temperature for 2 weeks at 1C / 1C, and record the discharge capacity in the first week after high temperature standing, the discharge capacity in the second week, the internal resistance and volume after storage. Calculate the capacity retention rate, capacity recovery rate, internal resistance growth rate and volume expansion rate of the battery after storage according to the following formula:

[0108] Capacity recovery rate = discharge capacity in the first week after high temperature standing / discharge capacity in the first week × 100%;

[0109] Volume expansion rate = (volume after storage - volume in the first week) / volume in the first week × 100%

[0110] Table 1 Electrochemical performance of experimental batteries in each group

[0111]

[0112] From the comparison of the data of Examples 1 to 6 and Comparative Examples 1 to 3 in Table 1 above, it can be seen that the functional additives prepared by the present invention can simultaneously ensure a higher capacity retention rate, a lower volume expansion rate and a lower internal resistance growth rate in high-temperature storage, and a higher capacity retention rate in normal temperature cycles and high-temperature cycles, compared with borate and phenyl borate additives.

[0113] Electrolyte acidity test:

[0114] Take 20g of the electrolytes prepared in Examples 1 to 6 and Comparative Examples 1 to 3 above respectively in a conical flask, weigh and record as mass m, add 1 to 2 drops of neutral red methylene blue mixed indicator, titrate with triethylamine ultra-dry acetonitrile solution with a concentration of c, record the titration volume V of the standard solution, and calculate the acidity of the electrolyte according to the following formula:

[0115] Electrolyte acidity (ppm) = 20.006 × 1000 × V × c / m;

[0116] The remaining electrolyte was placed in a clean and dry aluminum-plastic bottle, sealed and placed in a 60°C oven for three days, then the electrolyte was taken out and the acidity of the electrolyte was measured again according to the above method.

[0117] Table 2 Electrochemical performance of experimental batteries in each group

[0118]

[0119] From the data comparison of Examples 1 to 6 and Comparative Examples 1 to 3 in Table 2 above, it can be seen that the functional additives prepared by the present invention can delay the hydrolysis of phenyl borate additives in the electrolyte, and compared with the commonly used phenyl borate additives, can significantly inhibit the increase in acidity of the electrolyte during high-temperature storage.

[0120] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An electrolyte additive, characterized in that: One or more selected from the compounds having structures shown in Formula A-1, Formula A-2 and Formula A-3: In Formula A-1, Formula A-2 and Formula A-3, R1 and R2 are each independently selected from trifluoromethanesulfonyl imide and borosilane.

2. The electrolyte additive according to claim 1, characterized in that: The additive is selected from one or more of compound (I), compound (II) and compound (III); 3. A lithium ion battery electrolyte, characterized in that: The invention comprises a lithium salt, a non-aqueous organic solvent and an electrolyte additive, wherein the electrolyte additive is selected from the electrolyte additive according to any one of claims 1 to 2.

4. The lithium ion battery electrolyte according to claim 3, characterized in that: The lithium salt is selected from any one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate or lithium difluorobis(oxalatophosphate).

5. The lithium ion battery electrolyte according to claim 3, characterized in that: The non-aqueous organic solvent is any one or more of an organic ester solvent, an ether solvent, a sulfone solvent or a nitrile solvent.

6. The lithium ion battery electrolyte according to claim 3, characterized in that: The electrolyte additive also includes a second additive, which is selected from vinylene carbonate, ethylene carbonate, propylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 1,4-butane sultone, 2,4-butane sultone, N-phenylbis(trifluoromethanesulfonyl)imide, phenyl methanesulfonate, hydroquinone difluorosulfonate, methylene disulfonate, 1,3,5-triallyl isocyanurate, hexamethylene Any one or more of 1,2-diisocyanate, 2,4-toluene diisocyanate, 1,2-diisocyanatoethyl methacrylate, 2,4-toluene diisocyanate, vinyl sulfate, vinyl disulfate, propylene sulfite, triallyl phosphate, tripropargyl phosphate, tris(trimethylsilane)borate, tris(trimethylsilane)phosphate, tris(vinyldimethylsilane)phosphate, propyl diprop-2-ynyl phosphate, ethyl diprop-2-ynyl phosphate or tetramethylmethylene diphosphate.

7. The lithium ion battery electrolyte according to claim 3, characterized in that: include: 10 to 16 parts by weight of a lithium salt; 80 to 90 parts by weight of a non-aqueous organic solvent; 0.1 to 10 parts by weight of electrolyte additives.

8. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte is selected from the lithium ion battery electrolyte according to any one of claims 3 to 7.

9. The lithium-ion battery according to claim 8, characterized in that: The active material of the positive electrode is selected from any one of lithium cobalt oxide, lithium manganese oxide, ultra-high nickel ternary nickel cobalt manganese lithium, lithium nickel manganese oxide, lithium iron phosphate or lithium iron manganese phosphate, preferably ultra-high nickel ternary nickel cobalt manganese lithium; Preferably, the active material of the negative electrode is selected from any one of artificial graphite, natural graphite, lithium titanate, metallic lithium, silicon-carbon composite material or silicon oxide; preferably artificial graphite; Preferably, the diaphragm is selected from a polypropylene diaphragm or a polyethylene diaphragm; preferably a polyethylene diaphragm.

10. The lithium ion battery according to claim 8, characterized in that The charging and discharging voltage of the lithium ion battery is 3.0-4.2V.

Citation Information

Patent Citations

  • Polyorganosiloxane composition

    CN102174155A

  • Silane coupling agent containing carborane and preparation method of same

    CN107746410A

  • Preparation method of high-temperature-resistant boron-containing silicon resin

    CN113881055A

  • High-voltage lithium ion battery electrolyte and lithium ion battery

    CN114335724A

  • Active material for nonaqueous secondary battery negative electrodes, negative electrode arranged by use thereof, and nonaqueous secondary battery

    JP2015187985A

Cited By

  • Modified high-nickel positive electrode material adaptive to high-voltage system as well as preparation method and application of modified high-nickel positive electrode material

    CN122202257A